2013
DOI: 10.1016/j.clineuro.2013.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation, etiology, and survival in adult acute encephalitis syndrome in rural Central India

Abstract: Background Acute encephalitis syndrome (AES) is a constellation of symptoms that includes fever and altered mental status. Most cases are attributed to viral encephalitis (VE), occurring either in outbreaks or sporadically. We conducted hospital-based surveillance for sporadic adult-AES in rural Central India in order to describe its incidence, spatial and temporal distribution, clinical profile, etiology and predictors of mortality. Methods All consecutive hospital admissions during the study period were sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 27 publications
1
51
0
Order By: Relevance
“…A provincial hospital based study done in Vietnam found enteroviruses in CSF by real-time RT-PCR in 10% of children and in 8% of adults with a CNS infection25. A recent hospital-based study in central India reported 11% of the adult patients with CNS infection had enteroviruses26. In our study, 13% (n = 12) of the patients with CNS infection had enteroviruses.…”
Section: Discussionsupporting
confidence: 45%
“…A provincial hospital based study done in Vietnam found enteroviruses in CSF by real-time RT-PCR in 10% of children and in 8% of adults with a CNS infection25. A recent hospital-based study in central India reported 11% of the adult patients with CNS infection had enteroviruses26. In our study, 13% (n = 12) of the patients with CNS infection had enteroviruses.…”
Section: Discussionsupporting
confidence: 45%
“…Additional encephalitic arboviruses that lead to neuroinvasive disease with neurocognitive sequelae in American patients include SLEV, LACV, EEEV, and Powassan virus, with total case numbers in the hundreds [94][95][96][97]. Finally, worldwide, encephalitic arboviruses, including JEVand RVFV, cause neurologic illness at the rate of 50 to 100,000 cases/year with neurocognitive sequelae in survivors [98][99][100]. There are currently no diagnostic or treatment modalities for cognitive sequelae in patients that recover from arbovirus encephalitides.…”
Section: Recovery From Arbovirus Encephalitismentioning
confidence: 99%
“…Though these cases were originally presumed to be due to Japanese encephalitis virus, they turned out to be negative for JEV. A few investigations revealed enterovirus association with these encephalitis cases (Joshi et al, 2012;Joshi et al, 2013;Sapkal et al, 2009;Kumar et al, 2011;Kumar et al, 2012;Lewthwaite et al, 2010), but there is no consensus on the serotype/s associated with the disease. Similarly, a few epidemiological studies on aseptic meningitis and acute hemorrhagic conjunctivitis cases from different regions of the country have been reported (Gopalakrishna 2007; Kumar et al, 2013;Madhavan et al, 2000;Maitreyi et al, 1999;Satpathy et al, 1996;Shukla et al, 2010), but a detailed analysis needs to be carried out.…”
Section: Emerging Eneterovirus Infections and The Need For Active Rementioning
confidence: 99%
“…A major proportion of these cases appear to be of non-Japanese Encephalitis Virus etiology, and enteroviruses have been implicated (Kakkar et al, 2013;Kumar et al, 2011;Kumar et al, 2012;Fowlkes et al, 2008;Sapkal et al, 2009;Joshi et al, 2012;Joshi et al, 2013;Reingold et al, 2013) and there is a need for systematic detailed study of the disease (Kakkar et al, 2013). Though epidemics of hemorrhagic conjunctivitis and handfoot-and mouth disease associated with enterovirus infections are being reported in the news (Times of India 2013) frequently from different parts of the country, very few have been investigated (Deshpande et al, 2003;Gopalakrishna et al, 2007;Gopalakrishna et al, 2012;Maitreyi et al, 1999;Madhavan et al, 2000).…”
mentioning
confidence: 99%